Knowledge and awareness level of Syrian dentists towards Novel Coronavirus pandemic: Cross-sectional study - Zuhair Al-Nerabiah; Muaaz Alkhouli; Mohannad Laflouf; Mahmoud Abdul-Hak (Universidad de Concepción., 2020)
Objetive: An outbreak of a novel and alarmingly coronavirus disease (COVID-19) was announced in China in December 2019, which later affected about 180 countries worldwide. Thus, this study aims to assess the awareness and attitude of dentists towards COVID-19 in Syria. Materials and Methods: The questionnaire was an online survey; it contained 19 questions formulated based on the information given by WHO and CDC for COVID-19. Study participants were dentists practicing in Syria. The questionnaire was translated into Arabic and published on the internet into multiple platforms. Results: 7233 dentists responded to the questionnaire; 64% of the participants were females. The majority of the respondents were general practitioner (78%), nearly half of the respondents had been practicing dentistry for at least 2-4 years (51%). The majority of the respondents has knowledge about COVID-19 and was aware it is contagious. Over half of the Syrian dentists received their information about COVID-19 from social media platforms (55%). Even though the majority of the dentists were aware that the incubation period could last up to 14 days, nearly half of the participants were not aware that symptomless patients can spread the virus (49%). Conclusions: Syrian dental practitioners were aware of COVID-19 definition, incubation period and prevention measures in the dental clinic. However, they had limited attitude regarding COVID-19 symptoms, mode of transmission and management.